Comparison of manual mycobacteria growth indicator tube and epsilometer test with agar proportion method for susceptibility testing of Mycobacterium tuberculosis - Karabulut, N.; Bayraktar, B.; Bulut, Y. (Elsevier, 2014)
Background and Objectives: Antimycobacterial susceptibility tests take weeks, and delayed therapy can lead to spread of Mycobacterium tuberculosis. Therefore, rapid, accurate and cost-effective methods are required for proper therapy selection. In this study, the Mycobacteria growth indicator tube (MGIT) and epsilometer test (Etest) methods were compared to the agar proportion method for susceptibility testing of Mycobacterium tuberculosis. Materials and Methods: The susceptibility tests against isoniazid (INH), rifampin (RIF), streptomycin (STM) and ethambutol (ETM) of 51 M. tuberculosis complex isolates were analyzed by the MGIT, Etest and agar proportion methods. Results: The concordance between MGIT/Etest and agar proportion methods was 98% for INH and 100% for RIF, STM, ETM. There were not statistically significant differences in results of the susceptibility tests between MGIT/Etest and the reference agar proportion method. Conclusion: The results have shown that MGIT and Etest methods can be used instead of the agar proportion method, because these two methods are more rapid and easier than the agar proportion method.
Keywords: Agar proportion method; epsilometer test; mycobacteria growth indicator tube; Mycobacterium tuberculosis